Small Bowel Obstruction Following Computed Tomography and Magnetic Resonance Enterography Using Psyllium Seed Husk As an Oral Contrast Agent. Issue 7 (2014) - Chen, Yingming Amy; Cervini, Patrick; Kirpalani, Anish; Vlachou, Paraskevi A; Grover, Samir C; Colak, Errol
Abstract : The authors report a case series describing four patients who developed small bowel obstruction following the use of psyllium seed husk as an oral contrast agent for computed tomography or magnetic resonance enterography. Radiologists who oversee computed tomography and magnetic resonance enterography should be aware of this potential complication when using psyllium seed husk and other bulking agents, particularly when imaging patients with known or suspected small bowel strictures or active inflammation.